2015
DOI: 10.5772/61606
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Vibrational Study of Folic Acid on Gold Nanopillar Structures Using Surface-Enhanced Raman Scattering Spectroscopy

Abstract: This paper presents a study of adsorption and vibrational features of folic acid, using surface-enhanced Raman scattering (SERS). A gold-capped silicon nanopillar (Au NP) with a height of 600 nm and a width of 120 nm was utilized to study the vibrational features of FA molecules adsorbed on the nanopillars within the high electromagnetic field areas. The adsorption behaviour of folic acid and the band assignment of the main vibrations together with the optimized geometry of folic acid and folic acid in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 25 publications
6
38
0
6
Order By: Relevance
“…This is in accordance with the study carried out by Su et al, which observed that these groups stabilized the nanoparticles through electrostatic repulsion [59]. It has been shown that the interaction of folic acid with the AgNPs occurs through the amino group of the pterinic ring of folic acid [7,8,31,59]. Besides, Castillo et al using the density functional theory to show that the Ag-FA interaction occurs mainly through the nitrogen of the pteridine ring.…”
Section: Silver Nanoparticles Functionalized With Folic Acidsupporting
confidence: 87%
“…This is in accordance with the study carried out by Su et al, which observed that these groups stabilized the nanoparticles through electrostatic repulsion [59]. It has been shown that the interaction of folic acid with the AgNPs occurs through the amino group of the pterinic ring of folic acid [7,8,31,59]. Besides, Castillo et al using the density functional theory to show that the Ag-FA interaction occurs mainly through the nitrogen of the pteridine ring.…”
Section: Silver Nanoparticles Functionalized With Folic Acidsupporting
confidence: 87%
“…Raman spectra of FA adsorbed on HA corresponding to FA adsorbed amounts of 9.7 μmol/m 2 (within domain I of the adsorption isotherm) and 24.4 μmol/m 2 (within domain II) are also reported ( Figure 6). Most of the vibrational bands from the Raman spectrum of pure FA are in concordance with the literature, 55,56 especially with bands in the range 600−1700 cm −1 . The most intense contribution is located at 1607 cm −1 and can be related to the stretching vibration of NH from the pteridine ring of FA.…”
Section: Resultssupporting
confidence: 87%
“…That is to say, FA can interact with the surface of the AuNP-FA through the carboxylate groups of glutamic acid portion and amine group of pterin moiety. Castillo et al [25] demonstrated that the FA interacts with gold-capped silicon nanopillars mainly through the nitrogen in the pterin moiety, when deposited a FA solution on gold-capped silicon nanopillars and did SERS and Raman analysis and DFT calculations. However, the z-potential near zero of the AuNP-FA could be related to the fact that the FA molecules are joined mainly by the carboxylic groups to the metal surface of the Au, leaving out the pterin ring (which at basic pH it has no charge).…”
Section: Resultsmentioning
confidence: 99%